Anomali Asas Non-Retroaktif dalam Kejahatan Genosida, Bertentangan dengan HAM? - Nurhidayatuloh Nurhidayatuloh; Akhmad Idris; Rizka Nurliyantika; Fatimatuz Zuhro (The Constitutional Court of the Republic of Indonesia, 2022)
The crime of genocide is one of the most serious international crimes stipulated in the Rome Statute. Previously, genocide was regulated in the Convention on Genocide entered into force on 12 January 1951. The convention and the Rome Statute do not allow retroactivity. However, retroactivity appears in the Indonesian Law on the Human Rights Court and is strengthened through the Indonesian Constitutional Court's Decision. This study focuses on the neglect of the non-retroactive principle in the Law on Human Rights Courts and the extent to which the retroactive period. This research uses normative-legal method with a statutory and case approaches. The result shows that ignoring the non-retoactive principle is contrary to international law and international human rights regulations. Hence, the Constitutional Court's decision that strengthens retroactivity can be interpreted that the Court maintains human rights while at the same time violates human rights by not accurately interpreting the word “derogation” and “restriction” in Article 28J of the 1945 Constitution.